2021
DOI: 10.3390/ijerph18073663
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Three Months Pilates Training on Balance and Fall Risk in Older Women

Abstract: This study assessed the effect of Pilates exercises on balance and fall risk in older women. Participants comprised 50 older women aged over 60 years, divided randomly into two groups: the experimental group (n = 30), which took part in Pilates sessions two times per week for three months, and the control group (n = 20). The control group did not participate in such sessions but also did not participate in any other rehabilitation programs or additional physical activity except everyday activities. Before and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 36 publications
0
29
0
1
Order By: Relevance
“…Across the 51 included studies, a total of 2,485 participants with a mean age of 66.5 ± 4.9 were considered ( 51 101 ). Altogether, 1,105 participants followed a PI, 725 participants were part of an IC group, and 636 joined an AC group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Across the 51 included studies, a total of 2,485 participants with a mean age of 66.5 ± 4.9 were considered ( 51 101 ). Altogether, 1,105 participants followed a PI, 725 participants were part of an IC group, and 636 joined an AC group.…”
Section: Resultsmentioning
confidence: 99%
“…ICs either instructed participants to stay with their normal activity level ( 51 , 52 , 56 , 57 , 59 , 60 , 66 , 67 , 71 , 78 , 82 , 85 , 87 , 89 , 93 , 96 , 101 ), to not exercise or train ( 53 , 68 , 69 , 72 , 76 , 79 , 90 92 , 94 , 95 , 99 ), to take part at a monthly meeting for communication ( 63 , 64 ), to attend educational workshops ( 97 , 100 ), or to take part in standard clinical care ( 65 ). The ACs' intervention approaches included an unspecific activity program ( 54 , 97 ), home exercises (for balance and strength) ( 55 , 75 ), a static stretching program ( 58 , 86 , 88 ), a muscular strength training ( 59 ), a resistance training ( 60 ), physiotherapy ( 61 , 62 ), a Proprioceptive Neuromuscular Facilitation Training ( 82 , 94 ), a traditional balance training ( 66 ), pelvic floor muscle training with anal electrical stimulation ( 69 ), unstable support surface exercises ( 70 ), walking ( 72 ), traditional exercising ( 73 ), suspension training with TRX ( 99 ), general physical activity program ( 98 ), clinical rehabilitation ( 74 , 77 ), Huber Training ( 80 ), aerobic exercises ( 83 ), Yo...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are in line with those of recent studies showing positive effects of Pilates on functionality [20,46,47]; moreover, none of the studies included in our review showed a negative ES for this outcome. Evidence sug-gests that Pilates improves functionality through postural stability [70], joint mobility [28], and strengthening of the muscular structures involved [49]. Consequently, a better score is achieved in ADLs by older people who perform Pilates.…”
Section: Discussionmentioning
confidence: 99%
“…They investigated the effects of three months of pilates training on balance and fall risks in older women. Their results showed statistically significant improvements in balance and risks of falling in old people [ 16 ].…”
Section: Discussionmentioning
confidence: 99%